PENERAPAN MOTODE DRILL UNTUKMENINGKATKAN KETERAMPILAN GERAK DASAR TARI ZAPIN SISWA KELAS IV SDN 97 PEKANBARU - Fenti Putri Sari Putri Sari; Zariul Antosa Antosa; Jesi Alexander Alim Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problems underlying this study is the low of student’s ability in Arts and Culture and Skills. This research aims to improve basic motion skills in teaching Zapin dance in study of Arts and Culture and Skills for IV grade students at SDN 97 Pekanbaru through the application of drill method. Subjects in this study were fourth grade students of SDN 97 Pekanbaru. Based on the analysis of the data shows the average value of the teacher’s activities on the first meeting of the first cycle was 56.25, and 68.75 for the second meeting. The first meeting of the second cycle increased to 75 and the second meeting of the second cycle becomes 87.5. While the percentage of students meeting the activity of the first cycle of the first 50%, at the second meeting increased to 62.5%, in the first meeting of the second cycle increased to 68.75%, and at the second meeting of the second cycle increased to 81.25%. Judging from preliminary data are still many students who have not reached the standard of skills in performing basic motion zapin dance with the number of students who are categorized less skilled amounted to 9 students (30%), skilled enough 17 students (56.67%) while students are considered skilled 4 students (13,33) with an average value of 49.9. After the implementation of the drill method, at the end of the first cycle of students who are skilled as many as 14 people (46.6%) and skilled enough 11 people (36.6%) and less skilled 5 students (16.66%) with the average classical value 58, while the final value of the second cycle students who are highly skilled totaling 14 students (46.6%), skilled 15 students (50%), and only one skilled enough students (3, 3%) with the average value increased to 78.8 of the first cycle. Based on the explanation above, it can be concluded that the application of the drill method can improve the basic skills of movement zapin dance for fourth grade students of SDN 97 Pekanbaru is acceptable. Key Word : Drill Method, Zapin Dance Basic Motion skills